Моделирование структуры данных информационной системы выявления ранних признаков нарушения механизмов гомеостаза биологической системы в экстремальных условиях - Порван, А. П.; Высоцкая, Е. В.; Новикова, И. В.; Макайда, С. В. (My University, 2017)
В статье предложено моделирование структуры данных информационной системы выявления ранних признаков нарушения механизмов гомеостаза биологической системы в экстремальных условиях на примере организма беременной, нарушение механизмов гомеостаза кото-рой может привести как к гибели плода, так и к смерти самой женщины. Полученные результаты могут быть использованы для исследова-ния процессов нарушения гомеостаза как биологических, так и экологических систем. Речь может идти о нарушениях, которые увеличи-вают риски возникновения различных угроз биобезопасности. У статті запропоновано моделювання структури даних інформаційної системи виявлення ранніх ознак порушення механізмів гомеостазу біологічної системи в екстремальних умовах на прикладі організму вагітної, порушення механізмів гомеостазу якої може привести як до загибелі плоду, так і до смерті самої жінки. Отримані результати можуть бути використані для дослідження процесів порушення гомеостазу як біологічних, так і екологічних систем. Мова може йти про порушення, які збільшують ризики виникнення різних загроз біобезпеки. The article suggests modeling the structure of the data of the information system for detecting early signs of the disturbance of the homeostasis mech-anisms of the biological system in extreme conditions by the example of automating the registration of pregnant women during the determination of premature births. These may include violations that increase the risks of various threats to biosafety. The developed data structure is openness, modi-fication and modularity of both the database. At the same time, aspects of the results, related to informatics, can be used to develop methods for for-malized description of the processes of disturbance of the homeostasis of ecological systems. These may include violations that increase the risks of various threats to biosafety. These results can be used in the development of test Biosystems allowing diagnosing such disorders homeostasis ecologi-cal systems.
Keywords: информационная система; беременность; преждевременные роды